Analysis of the role of pt ASDP Indonesia Ferry (Persero)'s training and development program to improving customer satisfaction - Indra Putri, Dian Fairizah; Sakapurnama, Eko (Technium Social Sciences Journal, 2023)
As a public service company, PT ASDP Indonesia Ferry (Persero) needs to improve the quality of human resources and service quality in order to maintain customer satisfaction. The type of study used is descriptive with a qualitative approach. This research was conducted to determine the role of the training and development program carried out by PT ASDP Indonesia Ferry (Persero) as an effort to improve the quality of service to the community. This study was design to show whether efforts to improve PT ASDP Indonesia Ferry (Persero)’s service quality are able to compete with their competitors.